Informator . no. 3, 1981 - Biuro Informacyjne Regionu Środkowo-Wschodniego NSZZ "Solidarność" (NSZZ "Solidarność" Region Środkowo-Wschodni, 1981)
Creation and circulation: After introduction of the Martial Law publication suspended. Republished underground in January 1982